Criminal Liability of Online Gamblers Based on the Roles of Bookies, Operators, Affiliates, and Players - Bara Libra Sagita; Gunardi Lie; Ade Adhari (jurnal.unprimdn.ac.id, 2026)
This study examines the criminal liability of online gambling perpetrators in Indonesia based on the roles of bookies, operators, affiliates, and players within the online gambling system. The analysis was conducted using a juridical-normative approach, examining regulations such as Article 303 of the Criminal Code and the ITE Law, as well as recent court decisions. The results show that levels of criminal liability vary based on the perpetrator's role, involvement, and intent, with bookies as the primary perpetrators bearing the heaviest responsibility. Operators and affiliates can be subject to criminal sanctions for facilitating and promoting online gambling activities. Players are subject to proportionate sanctions, taking into account aspects of awareness and socio-psychological factors such as addiction. Law enforcement faces challenges from technological developments, perpetrator anonymity, and jurisdictional boundaries, necessitating regulatory strengthening, law enforcement capacity building, cross-border cooperation, and public education. This study is limited to literature and regulatory analysis, therefore, empirical research is needed to delve deeper into socio-cultural issues and technical barriers in the field.